FORMAL ASSUMPTIONS OF THE STRUCTURAL EQUATION MODELS - SZYMAŃSKA, AGNIESZKA (Studia Psychologica: Theoria et praxis, 2016)
The purpose of this article is to describe the formal assumptions regarding the use of Structural Equation Models (SEM). Structural Equation Models are used to verify the theory and its assumptions. Five assumptions concerning construction of the measurement model, which precedes the verification of the theoretical assumptions with the aid of the structural equation model, were described. These are: a) checking the reliability of the latent variables, b) calculation of the variance of latent variable, c) checking the discriminant validity of the latent variables, d) checking the amount of factor loadings (lambd λ) and e) model fit statistics. In the next step, the one-level SEM model assumptions were discussed: a) turning off the paths of the model, b) checking the fit of the theoretical model to empirical data. For imaging of the content, graphs showing the measurement model and model SEM were presented.